Let's carefully review Izzie's steps and determine if she made any mistakes in solving the inequality \( 3(t+1)−4t≥−5 \).
Step 1: She correctly expanded the expression: \[ 3(t+1) - 4t \geq -5 \]
This simplifies to: \[ 3t + 3 - 4t \geq -5 \] So this step is correct.
Step 2: Continuing from Step 1: \[ 3t + 3 - 4t = -t + 3 \geq -5 \] This is also correct.
Step 3: From Step 2: To isolate \( -t \): \[ -t + 3 \geq -5 \] Subtract 3 from both sides: \[ -t \geq -8 \]
This was incorrectly simplified. So in this step, Izzie made a mistake. The correct inequality should be: \[ -t \geq -8 \] Now, multiplying both sides by -1 (which reverses the inequality): \[ t \leq 8 \]
Step 4: InIzzie's Step 4, she incorrectly solved: She said \( -t \geq -2 \) leads to \( t \leq 2 \), which is incorrect since she was wrong about what \( -t \) was equal to in the previous step.
Now, let's evaluate the statements:
- Izzie made a mistake going from step 2 to step 3: True
- Izzie made a mistake going from step 3 to step 4: True
- Izzie should not have changed the inequality symbol from ≥ to ≤: True (because she should have reversed the inequality when multiplying by -1)
- Izzie made a mistake going from step 1 to step 2: False (she was correct in step 1 to step 2)
- Izzie made no mistakes in solving this inequality: False (she made multiple mistakes)
So, the responses are:
- True
- True
- True
- False
- False